THE EVOLUTION OF CRITICISM. A HISTORICAL PERSPECTIVE (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract:This article focuses on the historical evolution of literary criticism, exploring how it has developed and transformed across different eras. From the philosophical and aesthetic foundations of ancient Greek thought to the complexities of modern post-structuralist and interdisciplinary approaches, it examines the key movements, theories, and figures that have shaped the field. By tracing this progression, the article highlights the dynamic relationship between literature, culture, and critical thought, showcasing how literary criticism has adapted to reflect changing societal, intellectual, and artistic contexts.